(C)onsumer focused (E)ducation on p(A)racetamol (S)ide (E)ffects, i(N)adequate (O)utcomes and (W)eaning (CEASE NOW) for individuals with low back pain: results of a feasibility study. Issue 11 (24th November 2022) - Patterson, Thomas; Turner, Justin; Gnjidic, Danijela; Mintzes, Barbara; Bennett, Carol; Bywaters, Lisa; Clavisi, Ornella; Baysari, Melissa; Ferreira, Manuela; Beckenkamp, Paula; Ferreira, Paulo
Abstract : Objectives: To determine the feasibility of a patient-education booklet to support patients with low back pain (LBP) to reduce paracetamol intake. Design: Single group, repeated measures feasibility study. Setting: Community. Participants: Adults experiencing LBP of any kind and self-reporting consumption of paracetamol for LBP weekly for at least 1 month were invited to participate. Intervention: Participants received a patient-education booklet 1 week after the baseline measures were collected. The intervention was designed to change beliefs, increase knowledge and self-efficacy to deprescribe paracetamol for their LBP and create discussion with a health professional through the mechanisms of motivation, capacity and opportunity. Primary outcome measures: Feasibility of recruitment procedures, data collection and acceptability of the intervention. Secondary outcome measures: Changes in motivation, self-efficacy, opportunity to deprescribe paracetamol for their LBP, paracetamol usage and LBP clinical outcomes at baseline, 1-week and 1-month follow-up. Results: A total of 24 participants were recruited into the study within the timeframe of 3 months from study advertisement and all completed the study follow-up. There were no missing data for any outcome measure across all follow-up points, 22 (91.6%) participants were willing to participate in a future randomised control trial (RCT) and over 60% of participants responded positively to questions regarding acceptability of the patient-educational booklet. Overall, at the 1-month follow-up, approximately two thirds (15/24) of participants had an increase in motivation and self-efficacy scores and had discussed or intended to discuss their paracetamol use for LBP with a health professional. Conclusions: The results of this study demonstrate that the patient-education booklet is feasible to implement, and both the intervention and study design were well-received by participants. This study supports the undertaking an RCT to assess the effects of the patient-education booklet on deprescribing paracetamol in people with LBP.